Biobank@VITO: Biobanking the General Population in Flanders - Van Den Heuvel, Rosette; Den Hond, Elly; Colles, Ann; Nelen, Vera; Van Campenhout, Karen; Schoeters, Greet (Frontiers in Medicine, 2020)
During the last 15 years, VITO has established an infrastructure for biobanking a collection of biological samples from the general population in Flanders (Belgium). This biobank was set up to contribute to future, yet unspecified, research questions in the field of environment and health. Biobank@VITO is a population biobank in which bio-specimen including human peripheral blood, cord blood and blood derivatives (e.g. serum, plasma, cells, RNA, DNA), urine, hair, nails, exhaled breath condensate, saliva DNA and human breast milk collected from non-diseased populations are preserved. Currently, the biobank stores about 70.000 samples from 7.700 individuals. These biospecimen were collected since 2002 in different human biomonitoring studies comprising European (e.g. DEMOCOPHES, HBM4EU), national (e.g. WHO human breastmilk studies), Flemish (Flemish Environment and Health Study (FLEHS) campaigns) and local (e.g. hotspots, 3xG project) well-defined and ethically approved research projects. Participants to the surveys included different age groups (newborns, children, adolescents and adults) and were representatively selected with regard to gender, age class, residence and/or socioeconomic status (SES). In each campaign, samples were stored in the Biobank@VITO. The registration, preservation and management of the samples in the biobank were done in a qualitative and uniform manner which guarantees the traceability of all samples. The samples in the biobank have an extended information backbone on the lifestyle, environment and health status of the donor. The biological samples in the biobank are an invaluable archive that can be used to address specific policy and research questions in the future, to test old samples with new technology and according to the latest methods and insights or to measure newly identified pollutants in old samples looking for long-term trends.